Islamic jurisprudence in the classical era - Calder, Norman (Cambridge University Press, 2010)
"Ten years after his untimely death, Norman Calder is still considered a luminary in the field of Islamic law. At the time he was one among a handful of scholars from the West who were beginning to engage with the subject. In the intervening years, much has changed, and Islamic law is now understood as fundamental to any engagement with the study of Islam, its history, and its society, and Dr. Calder's work is integral to that engagement. In this book, Colin Imber has put together and edited four essays by Norman Calder that have never been previously published. Typically incisive, they categorize and analyze the different genres of Islamic juristic literature that was produced between the tenth and fourteenth centuries, showing what function they served both in the preservation of Muslim legal and religious traditions and in the day-to-day lives of their communities. The essays also examine the status and role of the jurists themselves and are to be particularly welcomed for giving clear answers to the controversial questions of how far Islamic law and juristic thinking changed over the centuries, and how far it was able to adapt to new circumstances. In his introduction to the volume, Robert Gleave assesses the place and importance of Norman Calder's work in the field of Islamic legal studies. This is a groundbreaking book from one of the most important scholars of his generation"--Provided by publisher.